Analisis Manajemen Investasi Dalam Akumulasi Kekayaan Pak Wiryawan - , Riyan Helis Miroj ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Wealth Management spiked on the three pillars. Data discussion and analysis focused on the problems that occur on the client. Wealth management discussion of this thesis is more focused on the second pillar Wealth Growth and Accumulation more specifically on investment management. There are 3 general steps for observed this research. First is client profiling. Client profiling was getting information about balance sheet, cash flow statement and risk tolerance. Second was choosing the investment instrument, and the last one was implementing the new portfolio. Client on the year 2011 was 52 years old, who have problem on the asset allocation. Client just invests in property sector. The clientâs properties are 6 houses and 6 land. Assets allocations have focused on property can provide another impact on investment. There are two things that will be the result of the absence of different asset allocation. Two things are no less optimal spread of risk and return are obtained by suing only one asset class. This thesis discussed the problem and make financial check up in accordance with the client profile. Further evaluation of risk tolerance is done as an alternative basis point portfolio formulation. Formulation of the newly established portfolio based on risk and returns profiles to suit the client. Evaluation of risk tolerance based in the questionnaire of Grable and Layton, and obtained a score 18 means that the client including the conservative category. The selections for the category of conservative investment instrument are investments that have a low risk of such deposit, bonds and mutual funds. Rebalancing has been done to keep the clientâs portfolio performance remain good. Selection of financial assets became thought of learning by client further more.